Ville de Liège - Musée d'Art Moderne. (Liège : Museé d'Art Moderne Liège, 1985)
Angeli, Marc ; Bastianelli, Ariane ; Bianchini, Georges ; Bong, Rita ; Brissa, Christiane ; Collin, Jocelyne ; Corillon, Patrick ; Couvert, Jean-Paul ; Dutrieux, Daniel ; Fauconnier, Jean-Luc ; Freson, Florence ; Fourneau, Daniel ; Haenen, Toon ; Heselmans, Suzanne ; Hoornaert, Philippe ; Huylebroeck, Paul ; Joosen, Nic ; kluyskens, Bernadette ; Klenes, Anne-Marie ; Laboureur, Marianne ; Lizene, Jacques ; Mahieu, Jean-Marie ; Salmon, Marie-Odile ; Mahoux, Paul ; Massart, Jean-Georges ; Pace, Maria ; Parada, Laura Tamar ; Pierart, Pol ; Ransonnet, Jean-Pierre ; Rousseff, Juliette ; Rulmont, Marc ; Mathieu, Jean Spiroux - ; Schmetz, Francis ; Sowti, Kamran ; Tambour, Dani ; Torwesten, Dietrich ; Vandeloise, Guy ; Vandresse, Cécile ; Villers, Bernard
biografie
boek